Incorporating physical activity in mental health intervention service delivery: School psychologists' perspectives. Issue 4 (2nd October 2022) - Greenspan, Scott B.; Whitcomb, Sara; Gordon, Kelsey L.; Hayden, Laura; Lauterbach, Alexandra; Fefer, Sarah; Griffith, Catherine
ABSTRACT: Literature continues to suggest that physical activity is a viable modality in promoting positive mental health outcomes among youth. School psychologists may be well-positioned to incorporate physical activity within school-based mental health intervention service delivery. This study explores school psychologists' perspectives of using physical activity as a mechanism to support the mental health of students. Twenty practicing school psychologists participated in semi-structured focus groups and shared their perspectives on facilitators and barriers of promoting physical activity in schools to enhance mental health outcomes. Analytically, this study employed a grounded theory approach to yield themes that provide insight into the intersection of school psychology and physical activity. Results suggest that when school and district leaders prioritize using physical activity to promote mental health, this can in turn foster the development of (a) structures to foster such initiatives, (b) data collection and data-based decision-making efforts, and, in turn (c) effective and targeted interventions. Implications for research and practice are discussed.